1990
DOI: 10.1038/343076a0
|View full text |Cite
|
Sign up to set email alerts
|

Haemopoietic colony stimulating factors promote cell survival by suppressing apoptosis

Abstract: The survival, differentiation, proliferation and development of haemopoietic precursor cells and the functional activity of mature blood cells are all influenced by colony stimulating factors (CSFs). As haemopoietic cells rapidly die in the absence of appropriate CSF, the promotion of cell survival mediated by CSFs, or growth factors, is fundamental to all the other effects exerted by these factors. This enhancement of cell survival is distinct from the stimulation of proliferation. Here we show that the death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
370
2
11

Year Published

1996
1996
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 879 publications
(392 citation statements)
references
References 24 publications
9
370
2
11
Order By: Relevance
“…For instance, the enhancement of cell survival actively suppressing the process of apoptosis is distinct from the stimulation of proliferation. 3 For the purpose of convenience, the cytokines and the cell lines are arranged in Table 2 in alphabetical order (and not according to common functional aspects of the cytokines or their receptors or to a common origin of the cell lines). Examples of detailed cytokine response profiles are given for the well-known and most often used growth factor-dependent cell lines, namely M-07e and TF-1 (Figure 2).…”
Section: +10%mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the enhancement of cell survival actively suppressing the process of apoptosis is distinct from the stimulation of proliferation. 3 For the purpose of convenience, the cytokines and the cell lines are arranged in Table 2 in alphabetical order (and not according to common functional aspects of the cytokines or their receptors or to a common origin of the cell lines). Examples of detailed cytokine response profiles are given for the well-known and most often used growth factor-dependent cell lines, namely M-07e and TF-1 (Figure 2).…”
Section: +10%mentioning
confidence: 99%
“…This rapid cell death occurs by an active cellular ietic cells presents difficulties for the identification of cytoprocess (apoptosis) that can be suppressed by new addition kines with specific effects on certain types of cells and at the of growth factors. 3 Most of these cell lines showed a growth various stages of activation, proliferation or differentiation.…”
mentioning
confidence: 99%
“…DNA damage) further supports this view. Moreover, it has been reported that differentiated haematopoietic cells are less prone to apoptotic death than their undifferentiated precursors (Williams et al, 1990). In this scenario, it might be speculated that forced expression of wt-p53 normalizes the cellular functions of leukaemia cells and allows them to respond to intracellular signals, which drive the cell to apoptosis or differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that withdrawal of IL-3 from progenitor cell lines or primary IL-3 dependent bone marrow derived cells resulted in apoptosis of these cells (Collins et al, 1992;Williams et al, 1990) indicates anti-apoptosis activity of IL-3 in hematopoietic cells. Our analysis of the anti depletion-induced apoptosis activity of GM-CSF in mouse IL-3 dependent BA/F3 cells (Palacios and Steinmetz, 1985) showed the same requirement of the bc region as for proliferation promotion (Liu et al, 1999b,c).…”
Section: Introductionmentioning
confidence: 99%